Currents in the Eastern Mediterranean - Engel, I. (The International Hydrographic Review, 2015)
Ships have been ploughing through the Eastern Mediterranean since time immemorial. The “ sea-dogs ” of olden times were certainly not unprovided with information about the currents in this region. However, literature on this subject has up till now been rather rare.